An Efficient FEM-SFEM Iterative Coupling Procedure for Elastodynamic Problems - Arroyo Silva, Jonathan E. (2017)
In the present work, an efficient iterative coupling methodology between the Finite Element Method (FEM) and the Spectral Finite Element Method (SFEM) for the modeling of elastodynamic problems in the time domain is presented. The methodology allows the use of a nonconforming mesh at the interface between the subdomains, as well as independent time-step sizes within each subdomain. By minimizing a square error functional, an adaptive strategy for the relaxation parameter can be established in the iterative process, increasing the efficiency of the FEM-SFEM coupled analysis. Numerical simulations are presented in order to illustrate the accuracy and potentialities of the proposed methodology.